Project-Based Learning to Improve Problem Solving Skills in Early Childhood - Mufadilah, Suliatul; Anggraini, Henni; Haryono, Sarah Emmanuel (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2025)
Problem-solving skills are important for cognitive development in early childhood. At PAUD KB 'Aisyiyah 6 Wagir, many 5-6 year old children rely heavily on teacher guidance and lack initiative. This shows that current learning strategies do not promote independence or critical thinking. Hence, Project-Based Learning is suggested as a way to encourage problem-solving. This study aims to determine the improvement of problem-solving skills in early childhood through the implementation of project-based learning at PAUD KB 'Aisyiyah 6 Wagir. The research employed a Classroom Action Research (CAR) method using the Kemmis and McTaggart model, conducted in two cycles. The subjects of the study were 12 children aged 5–6 years enrolled in Group B at PAUD KB 'Aisyiyah 6 Wagir during the second semester of the 2024/2025 academic year. The research instrument used was an observation sheet based on the indicators outlined in the Regulation of the Minister of Education and Culture No. 146 of 2014, namely: (1) identifying problems, (2) finding alternative solutions, and (3) solving problems independently. The results showed that the average problem-solving ability of the children increased significantly from 57.4% in the pre-cycle, to 71,3% in the first cycle, and reached 97.25% in the second cycle. The implementation of the PjBL model encouraged the children to be more active, independent, creative, and capable of collaborating in solving real problems in their environment. Thus, project-based learning has proven to be effective in gradually and comprehensively enhancing early childhood problem-solving skills.